Study on life cycle of golden apple snail, Pomacea canaliculata, pest of rice - Saedon, Fharaazie Syahira (2013)
Malaysia produce eighty percent to support the population and import rice if still not enough for consumption which 82.3 kilograms of rice per year. Lately, several species of Apple Snails are serious pest of rice worldwide and had infected 6,000 hectares of paddy field in 2004. The objectives for this experiment which to determine the life cycle and to establish a rearing technique for Pomacea canaliculata, commonly known as Golden Apple Snail (GAS). The adult snails were collected from the rice field in Pulau Pinang and reared in the Glasshouse Unit and the Entomology Laboratory, Department of Plant Protection, Faculty of Agriculture of University Putra Malaysia. After GAS produce egg, five eggs cluster were put into petri dish for five cohorts. Twenty juvenile was transferred into five aquariums (32×18×26 cm) in the glasshouse. Parameters that recorded were the number of egg per cluster, hatched and unhatched snail, shell length, width and height of juvenile and adult, duration taken for snails mating, mortality and duration taken to complete life cycle of GAS. The distribution of number of eggs per cluster varies from 72 to 92 eggs per cluster with mean of 84.6±5.5. The hatching success of the eggs showed great variation with mean hatchability of 51.4±14.5 and the maximum hatching percentage of eggs observed was 75%. The growth parameters for 16 weeks showed a positive correlation between different growth parameters which are shell height (SH), shell length (SL) and shell width (SW) and the week duration. It also shows the growth pattern which upward growth continuously of snails which cause the linear graph is formed. The adults were observed only for snail mating at week-16 and no mortality of the snails occurred during this period.